RADIOCARBON IN GLOBAL TROPOSPHERIC CARBON DIOXIDE. Issue 4 (23rd August 2022) - Levin, Ingeborg; Hammer, Samuel; Kromer, Bernd; Preunkert, Susanne; Weller, Rolf; Worthy, Douglas E
ABSTRACT: Since the 1950s, observations of radiocarbon ( 14 C) in tropospheric carbon dioxide (CO2 ) have been conducted in both hemispheres, documenting the so-called nuclear "bomb spike" and its transfer into the oceans and the terrestrial biosphere, the two compartments permanently exchanging carbon with the atmosphere. Results from the Heidelberg global network of Δ 14 C-CO2 observations are revisited here with respect to the insights and quantitative constraints they provided on these carbon exchange fluxes. The recent development of global and hemispheric trends of Δ 14 C-CO2 are further discussed in regard to their suitability to continue providing constraints for 14 C-free fossil CO2 emission changes on the global and regional scale.